The Analysis of Technology Acceptance Model (TAM) on Culinary MSMEs Marketplace in Garut Regency - Hamdani, Nizar Alam; Muladi, Rio; Maulani, Galih Abdul Fatah (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The Objectives of this research are to examine the influence of perceived ease of use on perceived usefulness, the influence of perceived ease of use and perceived usefulness on behavioral intentions, the influence of behavioral intentions on usage behavior, the influence of subjective norms, and output quality. Demonstration Results of Perceptions of Usefulness and the Influence of Perceptions of Enjoyment on the Ease of Use of GoFood Marketplace among Culinary MSME Entrepreneurs in Garut Regency.Methodology: This research uses a quantitative approach and a survey method, which involves distributing a questionnaire to GoFood partner MSMEs in the Garut Regency. The collected data will then be analyzed using AMOS 27 software. The study focuses on Culinary MSMEs partnered with GoFood, or "merchants." A total of 275 respondents were sampled using a probability sampling technique called simple random sampling. The data collected in the research was taken from MSME actors who have used the Go Food Application platform in the Garut Regency.Finding: The results of this study indicate that (1) Perceived ease of use has an effect on perceived usefulness, (2) Perceived ease of use has no effect on behavioral intention, (3) Perceived usefulness has an effect on behavioral intention, (4) Behavioral intention has an effect on use behavior, (5) Subjective norms affect perceived usefulness, (6) Job relevance has an effect on perceived usefulness, (7) Output Quality has no effect on perceived usefulness, (8) Result of Demonstration has no effect on perceived usefulness, and (9) Perceived Enjoyment has an effect on perceived ease of use. This explains that technology is strategic in increasing understanding of adopting technology which has an impact on business performance.Conclusion: Based on the study results, MSMEs in the Garut district have adopted the use and utilization of application features on GoFood in their business processes.